STUDENTS' FEAR OF ORAL ENGLISH PRESENTATION IN HIGHER EDUCATION - Kasmawati Arlan; Muhammad Zia Ul Hq; Herlina Daddi (FKIP Unismuh Makassar, 2022)
The purpose of this study was to determine the fear experienced or felt by students in oral English presentations and strategies used to overcome fear in oral English presentation. This type of research is qualitative using descriptive method. the sample in this study were students majoring in English education, semester 4 as many as 15 students. The power obtained by using a questionnaire and which is open-ended and then analyzed descriptively. The results of the research obtained are Student Fear of Oral English Presentations in Higher Education, students experience and feel types of fear which include fear of communication, fear of negative evaluation and fear of test. The strategy used in overcoming fear in oral English presentations are the first strategy that focuses on the problem called problem focused coping, for example exercise, making important notes, and seeking support and the second strategy that focuses on emotions is called emotion focused coping, for example self-control, staying away and positive thinking.